2008
DOI: 10.1177/1087054708316250
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term, Open-Label Safety and Efficacy of Atomoxetine in Adults With ADHD

Abstract: Results of this open-label study support the long-term efficacy, safety, and tolerability of atomoxetine for the treatment of adult ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 15 publications
4
47
0
1
Order By: Relevance
“…In other words, four or five patients need to be treated with a nonstimulant medication in order to obtain one positive outcome, as compared with two patients in some stimulant trials. Atomoxetine's short-term [26,27] and long-term openlabel data [28] include one of the longest periods (97 weeks) of systematic pharmacologic treatment published in adults with ADHD [27]. In an open-label continuation treatment study (N=384), the efficacy of atomoxetine for many individuals was maintained.…”
Section: Non-stimulant Class Medicationsmentioning
confidence: 99%
“…In other words, four or five patients need to be treated with a nonstimulant medication in order to obtain one positive outcome, as compared with two patients in some stimulant trials. Atomoxetine's short-term [26,27] and long-term openlabel data [28] include one of the longest periods (97 weeks) of systematic pharmacologic treatment published in adults with ADHD [27]. In an open-label continuation treatment study (N=384), the efficacy of atomoxetine for many individuals was maintained.…”
Section: Non-stimulant Class Medicationsmentioning
confidence: 99%
“…For other children, the symptoms continue and therefore treatments need to be continued into adolescence, and possibly even into adulthood. 2,34 There is a growing evidence base to support the use of methylphenidate and atomoxetine [34][35][36][37][38] in adults with ADHD and the management of ADHD in this age group is included in most current guidelines. 2,3,6 In general, when a child with ADHD turns 18 years old, the treatment should continue as before with periodic assessments and reviews.…”
Section: Use In Special Populationsmentioning
confidence: 99%
“…A recent 4-year open label study of 384 adult patients demonstrated statistically significant improvement in ADHD symptom scores with minimal side effects, demonstrating the long-term efficacy and safety of atomoxetine. 43 Despite being recommended as a first-line treatment for pediatric patients with ADHD because of its comparable efficacy with stimulant medications and low abuse potential, among adult patients its use has primarily been limited to patients with comorbid substance use, psychiatric and tic disorders. 32,44 Antidepressants have demonstrated less comparable efficacy than stimulants in the treatment of adult ADHD.…”
Section: Dovepressmentioning
confidence: 99%